Analisis Postur Kerja Karyawan Menggunakan Metode Rapid Upper Limb Assessment Di PT. BSM - Agustiyani, Noppy; Ainun Nisah, Firda (Fakultas Teknik Universitas Tulang Bawang, 2024)
PT BSM is a manufacturing company that has several employees who work with postures that do not meet ergonomic standards. The quality of this work posture is a key factor in assessing the work efficiency of employees at PT BSM. The research aims to assess the level of risk for PT BSM employees based on work posture to support the design of changes that are useful for reducing the risk of injury or employee discomfort. The research method used is the Rapid Upper Limb Assessment (RULA) method to assess the upper body position and posture of workers while working, especially within the ergonomics framework for lathe and Milling machine employees. The research results indicated that both employees had a low level of work posture risk, so it is recommended to evaluate work posture to ensure employee safety and comfort in carrying out their duties. Keywords: Ergonomics, Rapid Upper Assessment, Work Posture